2008
DOI: 10.1038/ajg.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for ERCP-Related Complications: A Prospective Multicenter Study

Abstract: Patient-related factors are as important as procedure-related factors in determining high-risk predictors for post-ERCP overall complications and pancreatitis. However, the risk factors for asymptomatic hyperamylasemia may be mostly procedure related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
328
19
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(410 citation statements)
references
References 39 publications
40
328
19
23
Order By: Relevance
“…Although ERCP is the gold-standard method of the diagnosis for biliary lesions, post-ERCP pancreatitis remains an important and sometimes fatal (2-15%) problem [Freeman et al 1996;Loperfido et al 1998;Wang et al 2009;Cheng et al 2006;Testoni et al 2010;Meister et al 2011]. On the other hand, EUS-FNA can be performed for pancreatic masses with high sensitivity and safety compared with ERCP [Yamao et al 2005;Hasan and Hawes, 2012].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ERCP is the gold-standard method of the diagnosis for biliary lesions, post-ERCP pancreatitis remains an important and sometimes fatal (2-15%) problem [Freeman et al 1996;Loperfido et al 1998;Wang et al 2009;Cheng et al 2006;Testoni et al 2010;Meister et al 2011]. On the other hand, EUS-FNA can be performed for pancreatic masses with high sensitivity and safety compared with ERCP [Yamao et al 2005;Hasan and Hawes, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…These results may not be sufficient for CCA patients with poor prognosis. In addition, ERCP is associated with critical adverse events such as acute pancreatitis [Freeman et al 1996;Loperfido et al 1998;Wang et al 2009;Cheng et al 2006;Testoni et al 2010;Meister et al 2011]. Improvements in the accuracy and safety of diagnostic modality are thus still required.…”
mentioning
confidence: 99%
“…ERCP is a demanding procedure associated with significant morbidity (6.85% of AEs) and occasional mortality (0.33%) [69][70][71]. AEs can be divided into general (in common with upper GI endoscopy) and specifically related to bilio-pancreatic handling (bleeding, perforation, infection and pancreatitis).…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp)mentioning
confidence: 99%
“…Th ese risk factors are additive and highlight the importance of refraining from performing ERCP in cases with marginal indication. Procedural factors have long been identifi ed as important, including pancreatic contrast injection, precut sphincterotomy, pancreatic sphincterotomy, and ampullectomy ( 6,7 ). Diffi cult cannulation with resultant papillary trauma has proven to be an independent risk factor, increasing with the number of cannulation attempts ( 5 ).…”
Section: Editorialmentioning
confidence: 99%
“…While it is widely thought that contrast injection into the pancreatic duct is a prime culprit in causing post-ERCP pancreatitis, recent studies have revealed that guidewire passage into the pancreatic duct (without subsequent pancreatic stent placement) is a major independent technique-related culprit ( 6,8,9 ). In the fi rst study ever to assess the independent role of PD wire passage, Wang and colleagues ( 6 ) performed a comprehensive evaluation of risk factors in 3,178 ERCP.…”
Section: Editorialmentioning
confidence: 99%